Modifikasi Business Model Canvas pada PT. Sarana Gadai Prioritas dalam Mempertahankan Kelangsungan Bisnis dan Antisipasi Pesaing Baru Bisnis Gadai High-End - Purwanto, Joko None; Indarto, Indarto; Wardoyo, Paulus (EconBank: Journal of Economics and Banking, 2023)
The research was conducted to determine the use of the business model canvas (modified) at PT. Sarana Gadai Prioritas to maintain the continuity of the high-end pawn business and to anticipate new competitors in the high-end pawn business. Where basically a high-end pawn business is a pawn business with a market segment and customers in the high-end category, which has its own community and has good prospects for development in the pawn business which is a very simple, easy and fast process with strong personal guarantees. have a relatively high value or goods in the category of luxury. This research was conducted using a qualitative deductive method, a case study (single), with the final result showing modifications and adjustments to the components in the business model canvas used by PT. Sarana Gadai Prioritas to run a pawn business with maintained business continuity and the emergence of risk management capabilities that support the performance of PT. Sarana Gadai Prioritas In this study, researchers used a qualitative approach with a case study approach (single) at PT. Sarana Gadai Prioritas, and seek meaning from the data obtained from the results of a detailed and in-depth study (case study). The results of this study are expected to provide a theoretical model concept of a strategy that can be applied in running a business model, especially for a pawn business like that run by PT. Sarana Gadai Prioritas with market segments and high-end customers and as a strategic and anticipatory step in anticipating the emergence of new competitors in the same market segment and customers